Potret Program Institutional Support System dalam Mendukung Ketercapaian IKU di Universitas Palangka Raya Tahun 2024: Portrait of the Institutional Support System Program in Supporting IKU Achievement at Palangka Raya University in 2024 - Hikmah, Nurul; Suprayitno, Suprayitno; Christina, Meilianna Devita; Rasan, Febriomico Griando; Sintha, Melia (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
As the oldest and largest tertiary institution in the Central Kalimantan region, Palangka Raya University (UPR) welcomes the policy of the Ministry of Education, Culture, Research and Technology (Kemdikbudristek) regarding Independent Learning Campus (MBKM). Since 2020, UPR has been aggressively socializing the MBKM policy to all faculties, units, and institutions at UPR. To ensure that MBKM activities at UPR are carried out well and produce quality output and outcomes, the Chancellor has established various policies about MBKM such as the Chancellor's Regulation on the Implementation of MBKM within Palangka Raya University, the Chancellor's Decree regarding Curriculum Guidelines for Supporting MBKM at UPR for 2022/2023, Chancellor's Decree regarding Implementation of UPR Collaboration Supporting MBKM Implementation, Chancellor's Decree regarding Technical Instructions for Implementing Learning in the Context of the MBKM Program at UPR. In 2023, UPR will form an MBKM study center which is under the organizational structure of the University Quality Assurance Institute. To encourage, accelerate, and facilitate the transformation of higher education, the Ministry of Education and Culture launched the Independent Campus Competition Program (PKKM) for study programs and the Institutional Support System (ISS) program for its universities/institutions. In 2024, Palangka Raya University, in a competition grant proposal, succeeded in passing 1 ISS program and 2 PKKM programs for the Bachelor of Laws study program, Faculty of Law and Bachelor of English, Faculty of Teacher Training and Education.